2020
DOI: 10.1016/j.nicl.2020.102454
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in alpha neurofeedback training efficacy predicts pain modulation

Abstract: Highlights Sensorimotor alpha neurofeedback training effect on pain perception was assessed. Neurofeedback training decreased the sensory-discriminative aspect of pain. Neurofeedback training increased the affective-motivational aspect of pain. Pain modulation by neurofeedback training was dependent upon the training efficacy. Neurofeedback training efficacy predicted sensory-discriminative pain modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The different methods used may thus introduce bias or render comparison between studies difficult (Chiang et al, 2008;Corcoran et al, 2018;Goljahani et al, 2012). In the field of NFB, studies target both the IAF (Alexeeva et al, 2012 ;Bazanova et al, 2013 ;Bobby & Prakash, 2017 ;Escolano et al, 2014 ;Grosselin et al, 2021 ;Hanslmayr et al, 2005 ;Nan et al, 2012 ;Wan et al, 2014 ;Zoefel et al, 2011) and the standard alpha frequency (Berger & Davelaar, 2018 ;Biswas & Ray, 2019 ;Bobby & Prakash, 2017 ;Brickwedde et al, 2019 ;Cho et al, 2008 ;Chow et al, 2017 ;Dekker et al, 2014 ;Guez et al, 2015 ;Hsueh et al, 2016 ;Lee et al, 2019 ;Nan et al, 2013 ;Nan et al, 2020 ;Naas et al, 2019 ;Nawaz et al, 2022 ;Peeters et al, 2014 ;Peng et al, 2020 ;Ros et al, 2010 ;Ros et al, 2013 ;Su et al, 2021 ;Takabatake et al, 2021 ;Wei et al, 2017). The advantage of IAF over standard alpha frequency, however, has still little empirical validation.…”
Section: High Alpha Neurofeedback Trainingmentioning
confidence: 99%
“…The different methods used may thus introduce bias or render comparison between studies difficult (Chiang et al, 2008;Corcoran et al, 2018;Goljahani et al, 2012). In the field of NFB, studies target both the IAF (Alexeeva et al, 2012 ;Bazanova et al, 2013 ;Bobby & Prakash, 2017 ;Escolano et al, 2014 ;Grosselin et al, 2021 ;Hanslmayr et al, 2005 ;Nan et al, 2012 ;Wan et al, 2014 ;Zoefel et al, 2011) and the standard alpha frequency (Berger & Davelaar, 2018 ;Biswas & Ray, 2019 ;Bobby & Prakash, 2017 ;Brickwedde et al, 2019 ;Cho et al, 2008 ;Chow et al, 2017 ;Dekker et al, 2014 ;Guez et al, 2015 ;Hsueh et al, 2016 ;Lee et al, 2019 ;Nan et al, 2013 ;Nan et al, 2020 ;Naas et al, 2019 ;Nawaz et al, 2022 ;Peeters et al, 2014 ;Peng et al, 2020 ;Ros et al, 2010 ;Ros et al, 2013 ;Su et al, 2021 ;Takabatake et al, 2021 ;Wei et al, 2017). The advantage of IAF over standard alpha frequency, however, has still little empirical validation.…”
Section: High Alpha Neurofeedback Trainingmentioning
confidence: 99%
“…Individual variations іn alpha neurofeedback training have been linked tо the efficacy оf neurofeedback training іn pain regulation. Individuals who exhibited positive responses tо neurofeedback training experienced a reduction іn pain and an augmentation іn the regulation оf SMR intensity, along with improved functional communication between motor and somatosensory regions ( Peng et al, 2020 ). Research has shown that the use оf neurofeedback tо modulate neural activity voluntarily could be a possible therapy for chronic conditions characterized by dysregulation оf both peripheral and central neural systems, such as fibromyalgia ( Goldway et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in this issue show the clinical potential of alpha neurofeedback training in reducing pain ( Peng et al, 2020 ), frontal gamma neurofeedback in improving working memory in schizophrenia ( Singh et al, 2020 ), and training to modulate slow cortical potentials relative to treatment as usual resulted in improvement in core symptoms of autism ( Konicar et al, 2021 ).…”
Section: Clinical Trialsmentioning
confidence: 99%